METHOD OF TAFSIR: METHOD OF MANTUQ AND MAFHUM - Amelia Monasari Nst; Alwizar Alwizar (PT. Intelek Cendikiawan Nusantara, 2025)
The rules of mantuq and mafhum interpretation are important foundations in the hermeneutics of the Qur'an to extract the meaning of zahir and khafi, especially in dealing with modern issues such as Islamic biomedical ethics and sharia finance that require adaptive laws to remain based on nash. This research carries the aim of elaborating the definition of mantuq and mafhum, explaining their implementation in istinbath fiqh, and highlighting their relevance to counteract misinterpretation, through a descriptive-analytical approach based on thematic interpretation that analyzes the recitation of the Quran, the principles of ushul fiqh, along with illustrations of verses such as QS. Al-Baqarah: 43, 173; Al-Isra: 23-24; and Al-An'am: 145. The main results outline the classification of mantuq into nash, zhahir, muawwal, followed by mafhum which is divided into muwafaqah (fahwa khitab and lahnal khitab) plus mukhalafah (six variants: shifat, illat, adad, ghayah, hasr, laqab), which are accepted as hujjah by the majority of fuqaha except zhahiri, thus minimizing distortion of interpretation and strengthening contextual laws.